Automated Technology for Verification and Analysis 9th International Symposium, ATVA 2011, Taipei, Taiwan, October 11-14, 2011. Proceedings - Bultan, Tevfik; Hsiung, Pao-Ann (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 9th International Symposium on Automated Technology for Verification and Analysis, ATVA 2011, held in Taipei, Taiwan, in October 2011. The 23 revised regular papers presented together with 5 invited papers, 11 short papers, and 2 tool papers, were carefully reviewed and selected from 75 submissions. The papers address all theoretical and practical aspects of automated analysis, verification and synthesis; thus providing a forum for interaction between the regional and the international research communities and industry in the field.